(untitled) (The South East European Journal of Economics and Business, 2018)
Guided by managerial theory and behavioural economics, as well as the literature on exporting, this study combines the upper echelons perspective with the Melitz model to analyse the export behaviour of firms. Thus, it controls for the influence of managerial characteristics, neglected so far in the literature on firms’ export choice and degree in transition countries. The empirical analysis is based on a random sample of 500 Kosovan SMEs. Results provide support for the key hypothesis that both subjective and objective managerial characteristics are crucial for export decisions. In line with the strategic choice paradigm and behavioural economics, findings provide support for the influence of the habituation and rational expectations effect, as well as manager’s education and international exposure on export performance. Further, Kosovan firms are self-selective in their export behaviour in terms of productivity supporting the Melitz model. However, no evidence is found for the significance of institutional factors, even after performing factor analysis.